THE INFLUENCE OF THE NHT TYPE COOPERATIVE LEARNING MODEL ON MATHEMATICS LEARNING OUTCOMES OF CLASS III CLASS MIS JIHAN ULFANI - Khairiza Ulfa; Siti Rahmadhani (IAIN Bengkulu, 2023)
The purpose of this study is to see how the NHT type of cooperative learning model affects the mathematics learning results of class III pupils at MIS Jihan Ulfani. The population of this study consisted of 332 students from class III MIS Jihan Ulfani. Random sampling was used to choose the research sample of 74 people. This study employs a single factor independent groups design. The test approach was used to obtain data on critical thinking skills and mathematics learning outcomes. MANOVA is used to analyze data. The results showed that: (1) there was a significant effect of the NHT type of cooperative learning model on critical thinking skills, (2) there was a significant effect of the NHT type cooperative learning model on mathematics learning outcomes, (3) there was a significant effect of the type of cooperative learning model NHT simultaneously on critical thinking skills and mathematics learning outcomes. Thus, it can be concluded that the cooperative learning model of the NHT type has a positive effect on critical thinking skills and mathematics learning outcomes for class III students of MIS Jihan Ulfani.